What are the perceptions of perfectionism is a Girls' Boarding house - George, Charlotte (2016)
My research aims to explore the perceptions of perfectionism among girls in Year 10 and 11, from the same boarding house. Perfectionism in children and adolescents is becoming a more thoroughly researched area, especially as media attention on the negative effects of perfectionism is increasing. My research seeks to develop a deeper understanding of how pupils perceive and experience perfectionism, whether this reflects the patterns found in the literature and to suggest improvements to professional practice based on my results. The data in my study was obtained through mixed methods; a quantitative account of the level and type of perfectionism show by my participants, using the Child and Adolescent Perfectionism Scale (CAPS; Flett et al, 1997) and a qualitative account of their perceptions of perfectionism through semi-structured interviews. The results suggest that although reported levels of perfectionism from the CAPS were not high in comparison with existing data, the overall perception of perfectionism was negative. Social difficulties attributed to perfectionism were also particularly noteworthy. My methods illustrated the difficulty in relying on quantitative methods alone when studying perfectionism, and the value of further exploration of these complex issues using qualitative means. Based on my results, suggested improvements for future professional practice include a series of intervention strategies, perhaps conducted in